2013
DOI: 10.1007/s00484-013-0749-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seasonal and climate variations on calves’ thermal comfort and behaviour

Abstract: The aim of this study was to measure the effect of season and climate variations on thermal comfort and behaviour of 6-month-old dairy calves housed in a semi-opened shelter to develop animal-based indicators for assessing animal thermal comfort. The ultimate purpose was to further exploit the use of those indicators to prevent thermal stress by providing appropriate care to the animals. Measurements were taken for winter and summer seasons. Results showed that season significantly influenced (P ≤ 0.01) the ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
0
14
0
3
Order By: Relevance
“…Interestingly, standing and lying in cows is influenced by environmental factors, with lying time decreasing under conditions of heat stress (Cook et al, 2007), likely in an attempt by the cow to facilitate evaporative cooling. Similarly, calves spend more time lying in winter than in summer (Tripon et al, 2014). It could be speculated that differences in perception of thermal comfort may have influenced some activity patterns in the present study, considering that calves born to HT cows spent less time standing and also tended to have higher rectal temperatures.…”
Section: Activity Patterns and Behavior During Early Life And Weaningmentioning
confidence: 64%
See 1 more Smart Citation
“…Interestingly, standing and lying in cows is influenced by environmental factors, with lying time decreasing under conditions of heat stress (Cook et al, 2007), likely in an attempt by the cow to facilitate evaporative cooling. Similarly, calves spend more time lying in winter than in summer (Tripon et al, 2014). It could be speculated that differences in perception of thermal comfort may have influenced some activity patterns in the present study, considering that calves born to HT cows spent less time standing and also tended to have higher rectal temperatures.…”
Section: Activity Patterns and Behavior During Early Life And Weaningmentioning
confidence: 64%
“…Understanding behavior is also a valuable tool when assessing animal welfare, and activity patterns are influenced by a range of factors, such as bedding material and comfort (Sutherland et al, 2014), and health (Proudfoot et al, 2014). Activity is also influenced by temperature: both calves and cows spend less time lying down in hot summer temperatures (Overton et al, 2002;Tripon et al, 2014). However, studies exploring the effect of in utero heat stress on the activity of dairy calves are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The monthly mean THI of Northern Japan was significantly lower than that of Southern Japan T (°C) -1.3 ± 0.5 -0.5 ± 0.7 3.3 ± 0.6 8.9 ± 0.5 14.4 ± 0.7 18.0 ± 0.2 22.3 ± 0.4 24.1 ± 0.3 19.9 ± 0.4 13.1 ± 0.5 7.1 ± 0.8 1.8 ± 0.6 RH (%) 80.5 ± 1.2 76.3 ± 1.9 71.0 ± 0.7 63.8 ± 3.0 70.5 ± 2.5 79.8 ± 2.1 80.3 ± 1.7 78.0 ± 1.2 75.8 ± 1.5 72.0 ± 1.6 75.0 ± 1.0 78.8 ± 1.9 THI 32.8 ± 0.8 34.6 ± 1.3 40.1 ± 1.0 49.1 ± 1.0 57.1 ± 0.9 63.4 ± 0.4 70.8 ± 0.4 73.6 ± 0.7 67.6 ± 1.6 56.6 ± 0.9 47.2 ± 0.7 36.8 ± 1.6 Southern Japan T (°C) 6.3 ± 0.3 4.6 ± 0.3 11.7 ± 0.4 16.1 ± 0.7 20.1 ± 0.3 22.4 ± 0.4 26.7 ± 0.6 27.3 ± 0.4 24.2 ± 0.6 19.9 ± 0.7 14.1 ± 0.9 8.2 ± 1.0 RH (%) 72.5 ± 2.4 71.8 ± 1.8 71.3 ± 1.3 73.8 ± 3.7 73.0 ± 2.7 86.0 ± 2.1 81.0 ± 2.1 79.8 ± 2.5 80.3 ± 2.5 76.3 ± 2.2 80.0 ± 1.5 76.0 ± 0.7 THI 45.5 ± 0.4 47.6 ± 0.4 54.1 ± 0.6 60.3 ± 1.0 66.4 ± 0.4 71.0 ± 0.5 77.8 ± 0.6 78.7 ± 0.4 73.0 ± 0.5 65.6 ± 0.7 57.0 ± 1.4 47.8 ± 1.3 T: temperature; RH: relative humidity; THI: temperature-humidity index (Okada et al 1984). The capacity of cows to compensate for climatic effects may vary with the housing system (Tripon et al 2014). Thus, we assumed that the barn and management styles adapted to the environment of each region modify the impact of the external environments.…”
Section: Resultsmentioning
confidence: 99%
“…The differences between the weeks of the winter trial in lying time, bout frequency, and duration are difficult to explain. Steers have been reported to lie down more at lower temperatures (Redbo et al, 1996;Tripon et al, 2014), whereas calves have laid the same amount across 4 different ambient temperatures in controlled indoor environments (5, 9, 13, and 18°C;Schrama et al, 1993). The average minimum temperature during the outdoor winter trial for Tripon et al (2014) was 3°C.…”
Section: Lying Time and Space Usagementioning
confidence: 99%
“…Steers have been reported to lie down more at lower temperatures (Redbo et al, 1996;Tripon et al, 2014), whereas calves have laid the same amount across 4 different ambient temperatures in controlled indoor environments (5, 9, 13, and 18°C;Schrama et al, 1993). The average minimum temperature during the outdoor winter trial for Tripon et al (2014) was 3°C. However, the ambient temperatures experienced by calves in our winter trial were lower than in previous studies, and calves were older than reported by Schrama et al (1993).…”
Section: Lying Time and Space Usagementioning
confidence: 99%